The clinical case of successful combined treatment of refractory arterial hypertension. Case report - Tatiana D. Solntseva ("Consilium Medicum" Publishing house, 2021)
In recent years, there has been an increase of patients with arterial hypertension, one of the variants of which is refractory arterial hypertension. This unfavorable clinical variant of the course of hypertension worries clinicians, due to the higher risk of developing cardiovascular complications, realizing the need for a better control of blood pressure. The presented clinical case demonstrates the successful combined treatment of refractory hypertension using antihypertensive therapy and renal denervation.